(untitled) (Texas Journal of Philology, Culture and History, 2024)
A language is made up of in a special way, that special way creates literature. In addition to Dash ‘s definition, in Oxford Dictionary, language is defined as ― the system of communication in speech and writing that is used by people of a particular country or areal. Therefore, it is understood that while people communicate with one another, they use language and, in their language, they also use the elements of literature. As the term literature is very broad and quite subjective it is possible to suggest numerous definitions for it. The important thing here is that language and literature cannot be assumed as something totally independent from each other. Thus, in this language-literature combination, there are several literary devices or elements such as metaphor, simile, irony, personification and so on. Thanks to these devices, people can easily convey their messages to the others. Literary devices not only make the message meaningful but also decode the hidden feelings. Metaphor and simile are commonly used literary devices in communication and literature. Hence, they are quite useful and favorable in delivering the desired feeling or meaning. In this study, metaphors and similes as commonly used literary devices are going to be analyzed and taught through John Steinbeck ‘s selected novels of “Mice and Men” and “The Grapes of Wrath”.